Evaluation of Diuretic Activity and Phytochemical Contents of Aqueous Extract of the Shoot Apex of Podocarpus falcactus - Meharie BG; Tunta TA (Dove Medical Press, 2020)
Birhanu Geta Meharie,1 Tewodros Agedew Tunta2 1Department of Pharmacy, Wollo University, Dessie, Amhara, Ethiopia; 2Department of Pharmacy, Arba Minch University, Arba Minch, SNNPR, EthiopiaCorrespondence: Birhanu Geta MeharieDepartment of Pharmacy, Wollo University, Dessie, Amhara, EthiopiaEmail birhanugeta@gmail.comBackground: In Ethiopian folk medicine Podocarpus falcactus is used to treat stomachache, cancer, diabetes, and difficulty of urination. However, its diuretic activity has not been proven scientifically.Objective: To determine the diuretic activity and phytochemical contents of the aqueous extract of the shoot apexes of Podocarpus falcactus.Methods: The coarse powder of Podocarpus falcactus shoot apex was extracted by cold maceration using distilled water. Male rats were treated with distilled water, the standard drug (furosemide 10 mg/kg), and three different doses (100, 200, and 400 mg/kg) of the aqueous extract. The diuretic activity was determined by measuring parameters such as time to the first urination, volume, electrolyte concentration, and pH of urine. Electrolyte indices were calculated to elucidate the possible mechanism of diuresis. Additionally, qualitative and quantitative determination of phytochemicals in the plant extract was carried out.Results: The aqueous extract induced diuresis, natriuresis, and kaliuresis in a dose- and time-dependent manner as compared to the negative control. The extract at 200 and 400 mg/kg doses produced significant diuresis (p< 0.001) by the end of the fifth hour compared to the negative control. Excretion of sodium, potassium, and chloride also significantly (p< 0.001) increased following extract administration. In addition, there was a significant change in the pH of urine samples of the extract-treated group compared with the negative control. Qualitative and quantitative determination of phytochemicals revealed the presence of alkaloids, flavonoids, phenolics, and tannins with the value of 128.4 mg atropine equivalents (AE)/g, 142.23 mg quercetin equivalents (QE)/g, 196.84 mg gallic acid equivalents (GAE)/g, and 25.5 mg tannic acid equivalents (TAE)/g, respectively. The aqueous extract exhibited significant diuretic activity due to its phytochemical content, which could be used as a starting point for further studies.Conclusion: The aqueous extract showed significant diuretic activity and confirmed the folkloric use of Podocarpus falcactus.Keywords: alkaloids, flavonoids, phenolics, Podocarpus falcactus, rats, saluretic, tannins